Anthropometric and cardiovascular characteristics of young elite male handball players according to playing positions - Alexandra Cselkó; Zita László; Éva Tékus; Márta Wilhelm (Exercise and Quality of Life)
The purpose of the present study was to examine the anthropometric parameters and cardiopulmonary functions of young handball players in different playing positions. 15 male handball players from first division (mean age: 16.06±0.63 yrs) participated in our research who were divided by their playing positions. First anthropometric parameters, body composition and pulmonary functions in rest were measured. Then physiological changes of the players were tested with Bruce protocol. We found that wings differed the most in morphological characteristics from other players. We did not find significant differences in pulmonary functions among positions. The highest values of Tidal volume in the vita maxima test were found in pivots (2.82±0.15 l) which is significantly higher than Tidal volume of goalkeepers (p=0.006). The highest mean value of maximal oxygen uptake was recorded (73.93±9.41 ml/kg/min) in wings. Altogether in our study important differences were seen in physique and in performance also among young handball players.